Dermatofibrosarcoma Protuberans of Scalp - An Unusual Site of Occurrence - Jyotsna; V Shruthi Kamal; Shivarahini; Ruban Kumar (Dr. Annil Mahajan, 2023)
Dermatofibrosarcoma protuberans [DFSP] is a low to intermediate soft tissue sarcoma arising from the skin dermis. DFSP of the scalp is very rare and is often confused with an epidermoid cyst. Patient Concern: Women reported with a swelling on the scalp for 6 months. Rational: The purpose of the report is to highlight the variable presentations of DFSP. Report: We report a case of DFSP of the scalp in a middle-aged woman. Diagnosis: The lesion histologically showed spindle-shaped cells and was positive for S100 and Ki 67 and negative for CD34. Outcome: The lesion was excised and the margins were negative for tumor cells. The patient was followed up for 2 months and there were no recurrences reported. Lessons: One must be aware of this uncommon entity and always perform a wide excision for these tumors to reduce the risk of recurrence.